Предмет: Математика,
автор: Ekaterinka0
Разложить на множители:
(х-1)/(√х-1)-(х-25)/(√х+5)
Ответы
Автор ответа:
0
(х-1) / (√х-1) - (х-25) / (√х+5) = ((√х)²-1²) / (√х-1) - ((√х)²-5²) / (√х+5) =
= (√х-1)(√х+1) / (√х-1) - (√х-5)(√х+5) / (√х+5) = (√х+1) / (√х-5) = (√х+1)(√х-5)⁻¹
= (√х-1)(√х+1) / (√х-1) - (√х-5)(√х+5) / (√х+5) = (√х+1) / (√х-5) = (√х+1)(√х-5)⁻¹
Похожие вопросы
Предмет: История,
автор: yurashirokov05
Предмет: Биология,
автор: RayDragnil
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: SanicCumonStepItOut
Предмет: Обществознание,
автор: максим1177535